2016
DOI: 10.1152/ajpcell.00309.2015
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 is a checkpoint regulator in hypoxia-induced astrocyte apoptosis via Ras/Raf/ERK pathway

Abstract: Astrocytes, the most numerous cells in the human brain, play a central role in the metabolic homeostasis following hypoxic injury. Caveolin-1 (Cav-1), a transmembrane scaffolding protein, has been shown to converge prosurvival signaling in the central nerve system. The present study aimed to investigate the role of Cav-1 in the hypoxia-induced astrocyte injury. We also examined how Cav-1 alleviates apoptotic astrocyte death. To this end, primary astrocytes were exposed to oxygen-glucose deprivation (OGD) for 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 48 publications
(51 reference statements)
1
32
0
Order By: Relevance
“…Cav-1, a key protein abundant in astrocytes 21 , was implicated in several pathological processes, including apoptosis 23 , inflammation 43 , and autophagy 26 . Our study showed that PA treatment significantly reduced the protein levels of Cav-1 but not the mRNA levels in cultured hippocampal astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cav-1, a key protein abundant in astrocytes 21 , was implicated in several pathological processes, including apoptosis 23 , inflammation 43 , and autophagy 26 . Our study showed that PA treatment significantly reduced the protein levels of Cav-1 but not the mRNA levels in cultured hippocampal astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Cav-1 is essential for cellular survival, and its overexpression alleviated ischemic death of cortical neurons 51 and hypoxia-mediated apoptosis of astrocytes 23 . In our present study, we found that the overexpression of Cav-1 attenuated PA-caused apoptotic death, whereas the downregulation of Cav-1 dramatically worsened it, with no effect on necrotic death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of Cav-1 using Cav-1 small-interfering (si)RNA exacerbated astrocyte cell damage and impaired cellular glutamate uptake after oxygenglucose deprivation (OGD). In contrast, overexpression of the Cav-1 caveolin scaffolding domain peptide attenuated OGDinduced astrocyte apoptosis via ERK signaling (Xu et al, 2016), thus further demonstrating the importance of Cav-1 in BBB physiology (Gu et al, 2012;Fu et al, 2014).…”
Section: Brainmentioning
confidence: 91%
“…Within cellular components of the blood-brain barrier (BBB), Cav-1 regulates extracellular matrix proteins that include metalloproteinases (Virgintino et al, 2002) and tight junction proteins, which in turn modulate BBB physiology (Abbott et al, 2006;Gu et al, 2011;Liu et al, 2012;Lakhan et al, 2013;Zhao et al, 2014;Gurnik et al, 2016). Cav-1 has also been shown to be critical in hypoxia-induced astrocyte injury (Xu et al, 2016), which can lead to BBB damage and leakage. Knockdown of Cav-1 using Cav-1 small-interfering (si)RNA exacerbated astrocyte cell damage and impaired cellular glutamate uptake after oxygenglucose deprivation (OGD).…”
Section: Brainmentioning
confidence: 99%